Production and Comparison of Yields of Biodiesel from Food Waste and Cheap Sources to Identify Good Raw Material in India for Replacement Present Diesel Fuel - Jajoo, Rajkumar (International Journal of Scientific Research in Biological Sciences, 2023)
Particulate matter is a significant environmental threat because of its link to fossil-fuel-induced climate changes and harmful carbon dioxide emissions. The purpose of this research is to use food waste products and used cooking oil to power human needs while minimizing environmental damage. Using biofuel can help us protect the environment, reduce carbon dioxide emissions and reduce transportation cost as biofuel is substitute of petrol and diesel. We investigate waste-to-energy (thermal and biochemical) conversion techniques. The primary focus of this research is on advances in the field of "synchronous waste mitigation with energy development." In this article compares the yield of biodiesel production by using various raw materials. This research is conducted to finding quality raw materials which available easily in India for biodiesel production. Emphasizing the significance of organic molecules in the creation of cleans and renewable energy. The necessity for adequate and renewable fossil fuel alternatives is emphasized.